Effects of repeated pulsed herbicide exposures on the growth of aquatic macrophytes. (21st November 2012) - Boxall, Alistair B.A.; Fogg, Lindsay A.; Ashauer, Roman; Bowles, Teresa; Sinclair, Chris J.; Colyer, Alison; Brain, Richard A.
Abstract Many contaminants are released into aquatic systems intermittently in a series of pulses. Pulse timing and magnitude can vary according to usage, compound‐specific physicochemical properties, and use area characteristics. Standard laboratory ecotoxicity tests typically employ continuous exposure concentrations over defined durations and thus may not accurately and realistically reflect the effects of certain compounds on aquatic organisms, resulting in potential over‐ or underestimation. Consequently, the relative effects of pulsed (2 and 4 d) and continuous exposures of the duckweed Lemna minor to isoproturon, metsulfuron‐methyl, and pentachlorophenol over a period of 42 d were explored in the present study. At the highest test concentrations, exposure of L. minor to pulses of metsulfuron‐methyl resulted in effects on growth similar to those of an equivalent continuous exposure. For isoproturon, pulsed exposures had a lower impact than a corresponding continuous exposure, whereas the effect of pentachlorophenol delivered in pulses was greater. These differences may be explained by compound‐specific uptake and degradation or dissipation rates in plants and the recovery potential that occurs following pulses for different pesticides. Given these results, use of a simple time‐weighted average approach to estimate effects of intermittent exposures from short‐term standard toxicity studies may not provide an accurate prediction that reflects realistic exposure scenarios. Development of mechanistic modeling approaches may facilitate better estimates of effects from intermittent exposures. Environ. Toxicol. Chem. 2013;32:193–200. © 2012 SETAC